Thinking Faith Engagement beyond Faith: the Spiritual Dimension in the World Health Organization: Policy and Practice Note - Winiger, Fabian (Religion & development, 2024)
The preamble to the constitution of the World Health Organization (WHO) contains an often-cited definition of health as a “state of complete physical, mental and social well-being and not merely the absence of disease or infirmity.” Already at the inaugural meeting of the World Health Assembly in 1948, which formally founded the organization, it was noted that this definition did not mention a ‘spiritual dimension’ of health. Throughout the past 70 years of the organization’s existence, debates over the WHO’s holistic mandate and the relevance of ‘spirituality’ to its work have periodically surfaced. This article outlines six key moments in its history in which the lack of ‘spirituality’ in the WHO’s understanding of health was raised and attempts were made to introduce it in some manner. In the early 2000s, amid a broader shift in the UN milieu toward cooperation with religious actors, interest in the ‘spiritual dimension’ began to give way to the notion of ‘faith engagement’. This article raises the terminological ambiguity of the ‘spiritual dimension’ and critically discusses the potentially problematic aspects of the term ‘faith of health’ in WHO’s reckoning with its holistic mandate.